Structural basis of polycomb bodies - Šmigová, Jana; Jůda, Pavel; Krejčí, Jana; Raška, Ivan (Folia biologica (Praha), 2014)
The spatial organization of the cell nucleus into separated domains with a specific macromolecular composition seems to be the fundamental principle that regulates its functioning. Because of the importance of regulation at the nuclear level, the cell nucleus and its domains have been intensively studied. This review is focused on the nuclear domain termed the Polycomb (PcG) body. We summarize and discuss data reported in the literature on different components of the PcG body that could form its structural basis. First, we describe the protein nature of the PcG body and the gene silencing factory model. Second, we review the target genes of Polycomb-mediated silencing and discuss their essentiality for the structural nature of the PcG body. In this respect, two different schematic models are presented. Third, we mention new data on the importance of RNAs, insulator elements and insulator proteins for the structure of PcG bodies. With this review, we hope to illustrate the importance of understanding the nature of the PcG subcompartment. The structural basis of a subcompartment directly reflects its status in the cell nucleus and the mechanism of its function.
Keywords: Subcellular Fractions; Animals; umlčování genů; Humans; Gene Silencing; lidé; Cell Nucleus Structures; zvířata; struktury buněčného jádra; polycomb proteiny; Polycomb-Group Proteins; subcelulární frakce